2020
DOI: 10.1111/ijcp.13916
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of the severity of COVID‐19: A meta‐analysis

Abstract: The coronavirus disease 2019 (COVID-19) originated from Wuhan (Hubei state, China), carrying similar DNA structure to SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome) has spread throughout the world creating massive panic to the human life. 1,2 The disease has the worst feature to transmit from person to person, 3 considering this feature and its lofty infection rate on January 30, 2020, the World Health Organization (WHO) declared COVID-19 as a global emergency.To date, it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
6
32
1
2
Order By: Relevance
“…We also found some comorbidities were potentially high-risk factors for severe disease and this is consistent with other recent studies [53,55,[57][58][59]. For example, as a chronic respiratory illness, COPD has already led to airflow blockage and so raises the risk of respiratory complications like ARDS.…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…We also found some comorbidities were potentially high-risk factors for severe disease and this is consistent with other recent studies [53,55,[57][58][59]. For example, as a chronic respiratory illness, COPD has already led to airflow blockage and so raises the risk of respiratory complications like ARDS.…”
Section: Plos Onesupporting
confidence: 92%
“…Our analysis has shown that males, obese patients (BMI � 30kg/m 2 ), patients with advanced age or a smoking history faced a greater risk of having severe COVID-19. This finding has also been supported by some previous studies [52][53][54]. However, some of the results of one meta-analysis were not consistent with our analysis, since they found gender irrelevant to the severity of COVID-19, which may possibly be due to the relatively small sample size [55].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Elsewhere, increasing age, male gender, comorbidities (e.g., diabetes, lung disease) have also been associated with COVID-19 severity [ 22 24 ]. In addition, HIV infection appeared as a significant predictor of severity in this study though not reported in Western settings.…”
Section: Discussionmentioning
confidence: 99%
“…The small representation of patients aged more than 70 years in our sample might explain this finding. In a meta-analysis conducted by Rahman et al (2020), male gender, hypertension, diabetes, fatigue or myalgia, and smoking history were found to be risk factors for COVID-19 severity [ 22 ]. There are some differences in comparison with our results, which do not include smoking, hypertension as risk factors for severity.…”
Section: Discussionmentioning
confidence: 99%